Multiparametric MR imaging to assess response following neoadjuvant systemic treatment in various breast cancer subtypes: Comparison between different definitions of pathologic complete response. Issue 117 (August 2019) - Santamaría, G; Bargalló, X; Ganau, S; Alonso, I; Muñoz, M; Mollà, M; Fernández, PL; Prat, A
Abstract: Objectives: To validate the performance of multiparametric magnetic resonance (MR) imaging to assess pathologic response to neoadjuvant systemic therapy (NST) in various breast cancer subtypes considering two definitions of pCR: absence of any residual invasive cancer or DCIS (ypT0) and absence of invasive tumour cells (ypT0/is). Methods: Institutional review board–approved retrospective study, with waiver of the need to obtain informed consent. From January 2015 to June 2017, 81 women with 82 breast cancers undergoing NST were included. Eighteen lesions (22%) were immunohistochemically HER2-positive, 12 (15%) triple negative (TN), 42 (51%) luminal B-like and 10 (12%) luminal B-like/HER2-positive. Breast MR imaging was performed before and after NST. A comparative analysis considering pCR as ypT0 and ypT0/is was carried out. Performance of univariate and multivariate models to potentially predict pathologic response were evaluated. Results: ypT0 was attained in 23% (19/82) of cases and ypT0/is in 33% (27/82) of cases. In both scenarios, HER2-positive subtype achieved the best response, 53% and 48%, respectively. A significant relationship was found between late enhancement and pathologic response (p < 0.001) regardless of pCR definition. In the ypT0 scenario, mean ADC ratio in the pCR subgroup was significantly higher than that in the non-pCR subgroup (p = 0.021) but no significant relationship was noted in ypT0/is. A multivariate model including MR late enhancement, ADC ratio and tumor subtype identified pathologic response with 86% and 84% accuracy when ypT0 and ypT0/is were considered, respectively. Conclusion: MR imaging late enhancement and ADC ratio along with breast cancer IHC subtype identify pathologic response following NST with high accuracy, achieving the highest NPV in TN and HER2-positive tumors and the highest PPV in luminal B-like subtypes, regardless of the definition of pCR as ypT0 or ypT0/is. In light of these findings and given that residual DCIS does not have an impact on survival rates, ypT0/is seems to be the preferable definition of pCR.